2021
DOI: 10.3390/ijms221910804
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson Disease Protein 7 (PARK7) Is Related to the Ability of Mammalian Sperm to Undergo In Vitro Capacitation

Abstract: Parkinson disease protein 7 (PARK7) is a multifunctional protein known to be involved in the regulation of sperm motility, mitochondrial function, and oxidative stress response in mammalian sperm. While ROS generation is needed to activate the downstream signaling pathways required for sperm to undergo capacitation, oxidative stress has detrimental effects for sperm cells and a precise balance between ROS levels and antioxidant activity is needed. Considering the putative antioxidant role of PARK7, the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…GSEA analyses revealed significant MAPK and cAMP pathway gene set downregulation in the AR samples relative to the FTH sperm samples, in line with prior data indicating that these MAPK and cAMP pathways can regulate capacitation and AR induction in sperm . Parkinson’s disease protein 7 (PARK7) is an essential regulator of sperm motility, oxidative stress responses, mitochondrial function, and fertility. PARK7, also known as DJ-1, localizes to the head, anterior midpiece, and principal piece of human sperm, while it has also been observed on the surface of the equatorial segment in sperm from mammalian species including sheep, horses, rats, hamsters, rabbits, and cattle . While the exact role that PARK7 plays in sperm has yet to be fully clarified, it is believed to be linked to the oxidative stress response. , A positive correlation between PARK7 levels and sperm plasma membrane integrity, total motility, and SOD activity has been reported in humans .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…GSEA analyses revealed significant MAPK and cAMP pathway gene set downregulation in the AR samples relative to the FTH sperm samples, in line with prior data indicating that these MAPK and cAMP pathways can regulate capacitation and AR induction in sperm . Parkinson’s disease protein 7 (PARK7) is an essential regulator of sperm motility, oxidative stress responses, mitochondrial function, and fertility. PARK7, also known as DJ-1, localizes to the head, anterior midpiece, and principal piece of human sperm, while it has also been observed on the surface of the equatorial segment in sperm from mammalian species including sheep, horses, rats, hamsters, rabbits, and cattle . While the exact role that PARK7 plays in sperm has yet to be fully clarified, it is believed to be linked to the oxidative stress response. , A positive correlation between PARK7 levels and sperm plasma membrane integrity, total motility, and SOD activity has been reported in humans .…”
Section: Discussionsupporting
confidence: 79%
“…Given that spermatozoa are largely transcriptionally and translationally inactive, increases in gene expression are unlikely to explain observed differences in protein levels in these cells, instead suggesting that these changes are attributable to processes such as translocation, degradation, or protein modification. 27,62 More proteins were found to be downregulated following sperm incubation in the capacitation medium, and the requirement for protein degradation during the sperm capacitation process was regulated by Tyr-P levels, 25,63 with similar findings having been reported in the context of cattle sperm capacitation. 19 In addition, studies have shown that the abundance of three serine protein inhibitor (SERPINE) family members (SERPINA3-3, SERPINA3-3, and SERPINB6) was reduced in cattle fresh sperm under capacitation conditions, 19 whereas no changes in SERPINE expression were observed in the present study in the context of frozen−thawed sperm capacitation.…”
Section: ■ Discussionsupporting
confidence: 73%
See 3 more Smart Citations